The Effectiveness of Website-Based Learning Media in Improving Students' Science Literacy Skills in Grade X Biology Material - Saprudin; Rahmania Pamungkas (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
Science literacy is a critical 21st-century competency that remains low among Indonesian students. This study aims to test the effectiveness of website-based learning media in improving science literacy skills in 10th-grade biology. The method used was a quasi-experimental study with a nonequivalent control group design involving two classes: an experimental class and a control class. The research instruments consisted of pretest and posttest assessments of science literacy skills. Statistical analysis results indicate a significant improvement in students’ science literacy skills, evidenced by an increase in the average score from 74.9% on the pretest to 86.5% on the posttest. Meanwhile, the control class also experienced an increase from 71.5% to 79.9%. In addition, the implementation of learning in the experimental class was classified as high. Thus, website-based learning media are effective in improving students’ science literacy.